Explaining the acquisition performance of large-sized European mergers and acquisitions - Nieminen, Henri (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Despite the fact that mergers and acquisitions (M&A) have a clear goal to provide opportunities for acquirers to improve their performance, results from the various researches reveal that acquiring firms fail to benefit their shareholders. This has led to a recognized need to investigate more acquisition performance to specify and better understand the issues and factors that explain failure and success. In this study, we utilize multiple perspectives, including organizational behavior, financial and strategic perspectives, to determine important factors explaining the short- and long-term acquisition performance of acquiring firms. We provide a comprehensive analysis on the European large-sized M&As. Our data includes domestic and cross-border acquisitions, with over EUR 100 million deal value, involving acquirers in EU15 countries in the period 2001–2014. The time period is extended until the end of year 2015 to examine the long-term acquisition performance. Transaction related data, comprising 230 deals, was retrieved from Orbis, whereas the stock price and statutory accounts data was collected using Thomson One Datastream. The main empirical analysis are divided into three categories. First, we analyse the abnormal returns to acquirer firms around the announcement and rumour dates as well as over the long-term period by utilizing event study method. We show that the market reactions on rumours and announcements are not significantly different from zero. In contrast, we find that on average, corporate acquisitions are value destroying from the long-term post-acquisition perspective. Second, our analysis will assess the effects of the different transaction specific factors on the returns in the univariate two sample t-tests, which are extended to multiple regression models. We show that payment method, acquisition premium, legal system, cross-border and industry relatedness characteristics have statistically significant effect on the long-term post-acquisition performance. Third, by utilizing multiple regression model, we show that auction process and cash as a payment method have significant increasing effect on the amount of premium paid in acquisitions. We conclude that the results of this study and utilized perspectives on acquisition performance could be included in typical M&A process and in managerial decisions relating M&A strategy with a purpose to enhance acquisition target screening, bidding process and post-merger integration.